Transforming education in war contexts: the relevance of two critical pedagogy theories as educational tools-the pedagogy of discomfort and the pedagogy of oppression - Trujillo Vargas, José Jesús; Romero Acosta, Kelly; García Salas, Luisa María; Mateos Toro, Luis Miguel (Grao, 2025)
There is much literature about the consequences of the armed conflict in Colombia on the Mental health of people. Also, there is literature about the stressful life experiences of victims. Nevertheless, there are a few studies about the implications of intersectionality of diversity and social justice in armed conflict. The current work will describe 1) the concepts of diversity, intersectionality, and social justice. 2) some victimization experiences of the armed conflict contained in The Truth Commission, and 3) two critical pedagogy theories: the pedagogy of discomfort and oppression as educational tools to prepare citizens to oppose violence and social injustice. These critical pedagogies support the intent of emancipation and the search for social justice and societal transformation. Schools and universities can be crucial in improving social disparities, which minimizes the gap between privileged and disadvantaged groups, such as students belonging to ethnic minority groups or from low socioeconomic status. In the Colombian armed conflict, all socioeconomic statuses were affected. However, the most affected have been those from ethnic minority groups and poor people. Children, adolescents, and youths should be empowered to avoid not only being victimized again but also being victimizers.
Es un capítulo del libro: Gavilán-Martín, D., Baena-Morales, S., Álvarez-Herrero, J.F., Veramendi Villavicencios, N. (Coords.). (2025). Educación transformadora: innovación y didáctica para la sostenibilidad. Grao
Keywords: critical pedagogy; Freire; armed conflicto; Boler; social justice